Two new species of Graphocephala Van Duzee from Costa Rica (Cicadellidae: Cicadellinae) - Godoy, Carolina; Villalobos, William (Zootaxa, 2006)
The genus Grahocephala, which was described by Van Duzee (1916), is a large complex group distributed from southern Canada to Colombia, Venezuela, and French Guiana. Young (1977) revised the genus and described twelve new species. Later, Nielson and Godoy (1995) added five more species. In this paper two new species are described from Costa Rica: G. crusa and G. riverae. The first species showed positive DAS-ELISA results for the bacterium, Xylella fastidiosa.